Modified exorotation graft tension for tibial fixation in anterior cruciate ligament reconstruction: a randomized controlled trial (Medical Journal of Indonesia, 2018)
Background: The inability of anterior cruciate ligament reconstruction (ACLR) surgery to reduce tibial internal rotation causes many problems. A large tibial internal rotation will result in a patellofemoral pain syndrome. This study aimed to introduce a new technique of modified exorotation graft tension at tibial fixation to minimize endorotation, reduce tibial internal rotation, and prevent patellofemoral pain syndrome.Methods: This study was a randomized double-blind controlled clinical trial. ACL rupture patients underwent ACLR surgery between December 2014 and Februrary 2015. They were randomized to standard endorotation group or modified exorotation group. Hamstring autograft was used and fixed with an EndoButtonÂ® and bioabsorbable interference screw. Tibial tubercle to trochlear grove (TTTG) was used to evaluate rotation, whereas cartilage oligomeric matrix protein (COMP) was employed to analyze cartilage breakdown. The functional outcome was measured using the Kujala score to assess patellofemoral joint function. Evaluations were conducted before the surgery and at 6 months postoperation.Results: A total of 29 subjects were recruited. Sixteen subjects were allocated into the standard endorotation group, and 13 were assigned to the modified exorotation group. The exorotation group demonstrated better results than the endorotation group in all three parameters: TTTG (p=0.028), COMP (p<0.001), and Kujala score (p=0.015).Conclusion: A new technique of modified exorotation direction of graft tension for ACL reconstructive surgery at tibial fixation showed a significant reduction in tibial internal rotation and cartilage breakdown. The proposed method could significantly improve the functional outcome of those with total ACL rupture.